2018
DOI: 10.1371/journal.pone.0199108
|View full text |Cite
|
Sign up to set email alerts
|

Preclinical characterization of INCB053914, a novel pan-PIM kinase inhibitor, alone and in combination with anticancer agents, in models of hematologic malignancies

Abstract: The Proviral Integration site of Moloney murine leukemia virus (PIM) serine/threonine protein kinases are overexpressed in many hematologic and solid tumor malignancies and play central roles in intracellular signaling networks important in tumorigenesis, including the Janus kinase–signal transducer and activator of transcription (JAK/STAT) and phosphatidylinositol 3-kinase (PI3K)/AKT pathways. The three PIM kinase isozymes (PIM1, PIM2, and PIM3) share similar downstream substrates with other key oncogenic kin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
52
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(58 citation statements)
references
References 74 publications
1
52
0
Order By: Relevance
“…11 Efforts have begun to co-target PIM and the PI3K pathway, which has exhibited promising synergistic effects, with the combined therapy suppressing cell growth 35,81 and viability and increasing apoptosis 11 in comparison with monotherapies in PCa, 71 as well as in hematological malignancies. 11,82 Another study on human PCa cells 35 supported these findings, showing that combined therapy resulted in lower cell growth and survival than the monotherapies in vitro, as well as higher tumor shrinkage and reduced proliferation in mouse models. The study also presented evidence in favor of the relationship between PIM, mTORC1, NRF2 (nuclear factor erythroid 2-related factor, a molecule involved in response to oxidant stress), 83 and the resultant mechanisms of PI3K inhibitor resistance to apoptosis.…”
Section: Pim Inhibition Within the Prostate Cancer Clinical Pathwaymentioning
confidence: 87%
See 1 more Smart Citation
“…11 Efforts have begun to co-target PIM and the PI3K pathway, which has exhibited promising synergistic effects, with the combined therapy suppressing cell growth 35,81 and viability and increasing apoptosis 11 in comparison with monotherapies in PCa, 71 as well as in hematological malignancies. 11,82 Another study on human PCa cells 35 supported these findings, showing that combined therapy resulted in lower cell growth and survival than the monotherapies in vitro, as well as higher tumor shrinkage and reduced proliferation in mouse models. The study also presented evidence in favor of the relationship between PIM, mTORC1, NRF2 (nuclear factor erythroid 2-related factor, a molecule involved in response to oxidant stress), 83 and the resultant mechanisms of PI3K inhibitor resistance to apoptosis.…”
Section: Pim Inhibition Within the Prostate Cancer Clinical Pathwaymentioning
confidence: 87%
“…Early work suggests efficacy of the co-targeting strategy in myelofibrosis, leading to a clinical trial combining ruxolitinib, a JAK1/JAK2 inhibitor, with PIM447, a pan-PIM inhibitor 95 (NCT02370706), and another trial combining JAK1 inhibition (itacitinib) with a preclinical PIM inhibitor (INCB053914) in hematological malignancies. 82 Contrary to these results, another study found that inactivation of STAT3 or IL-6 (interleukin-6) could lead to quicker PCa progression, as it would prevent STAT3 stimulation of p14 (ARF) and its other tumor suppressor targets. 96 This evidence would argue that targeting STAT would not be beneficial for the patients, and high levels of STAT3 should be treated as a biomarker and not a therapeutic target.…”
Section: Pim Inhibition Within the Prostate Cancer Clinical Pathwaymentioning
confidence: 91%
“…PIM kinases can also regulate growth through continued activation of mTOR in parallel with the PI3K pathway [19]. Upregulation of PIM 1 expression has been shown in prostate cancer following inhibition of AKT [20], providing further evidence for the idea of crosstalk between both PIM kinase and PI3K/AKT/mTOR pathways [21]. Inhibition of AKT can also induce increased expression of several different receptor tyrosine kinases such as HER2 through PIM 1-mediated regulation [2,22].…”
Section: Introductionmentioning
confidence: 94%
“…IBL-302 is a first-in-class oral kinase inhibitor rationally designed to uniquely combine pan-PIM kinase, pan-PI3K and mTOR inhibition in a single agent. Currently, there are a number of different preclinical and phase I trials focused on PIM kinase inhibition [21,[23][24][25][26][27][28][29]; however, few have been successful, with a narrow therapeutic window, which resulted in a dose-limiting cardiac QTc prolongation (SGI-1776) [24] (NCT00848601) or other unintended off-target effects, resulting in lack of observed effect (AZD1208) [30] (NCT01588548). However, in combination with other inhibitors, preclinical and phase I clinical trials suggest more tolerability and higher efficacy for PIM kinase inhibitors [31,32].…”
Section: Introductionmentioning
confidence: 99%
“…Proviral integration site for Moloney murine leukemia virus-1 (PIM-1) is a serine/threonine kinase, involved in cell cycle progression, cell growth, cell survival and therapy resistance. PIM-1 is activated in various types of cancer, amongst which prostate [14][15][16] , colorectal [15,[17][18][19] , triple negative breast cancer (TNBC) [20,21] , hematologic malignancies [22][23][24] , neuroblastoma [25] and lung cancer [26] . For this reason, PIM kinases could provide a common target for the treatment of diverse malignancies.…”
Section: Introductionmentioning
confidence: 99%